An Integrative Literature Review of Organizational Learning Culture and Performance - Sumi Lee (Adult Education Research Conference, 2023)
Despite intense interest in the correlation between organizational learning and performance in the HRD field, few attempts have been made to review and critiques to synthesize the current literature. This study aims to explore the effectiveness of learning organizational culture and performance using the integrative literature review method. The authors then provide a critique of the state of the organizational learning culture literature and outline targeted suggestions to guide practice and future empirical, theoretical work.
Keywords: Organizational leanring culture; Performance.